PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR IPAS SISWA KELAS V UPT SPF SD NEGERI PARANG TAMBUNG 1 KECAMATAN TAMALATE KOTA MAKASSAR - Andi Makkasau; Rosdiah Salam; Hartati Embong Bulan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The problem in this study is the low learning outcomes of fifth-grade students of the UPT SPF of Parang Tambung 1 State Elementary School. This study aims to describe the application of the Project Based Learning (PJBL) learning model in improving the learning outcomes of fifth-grade students of the UPT SPF of Parang Tambung 1 State Elementary School, Tamalate District, Makassar City. The method used is a qualitative approach with the type of Classroom Action Research (CAR). The study was conducted at the UPT SPF of Parang Tambung 1 State Elementary School, Tamalate District, Makassar City, with research subjects consisting of a teacher and 27 students consisting of 13 male students and 14 female students. Data collection techniques include observation, tests, and documentation, while data analysis is carried out descriptively qualitatively. The results of the study show that teacher activity in the learning process in cycle I is in the sufficient category, and has increased in cycle II to the good category. Student learning activities also show an increase, from the sufficient category in cycle I to the good category in cycle II. Student learning test results have increased, from the sufficient category in cycle I to the good category in cycle II. The conclusion of this study shows that the application of the Project Based Learning (PJBL) learning model can improve the science learning outcomes of fifth grade students of UPT SPF, Parang Tambung 1 Elementary School, Tamalate District, Makassar City.